1998
DOI: 10.1128/mcb.18.3.1725
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through CD5 Activates a Pathway Involving Phosphatidylinositol 3-Kinase, Vav, and Rac1 in Human Mature T Lymphocytes

Abstract: CD5 acts as a coreceptor on T lymphocytes and plays an important role in T-cell signaling and T-cell-B-cell interactions. Costimulation of T lymphocytes with anti-CD5 antibodies results in an increase of the intracellular Ca2؉ levels, and subsequently in the activation of Ca 2؉ /calmodulin-dependent (CaM) kinase type IV. In the present study, we have characterized the initial signaling pathway induced by anti-CD5 costimulation. The activation of phosphatidylinositol (PI) 3-kinase through tyrosine phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 70 publications
5
47
0
Order By: Relevance
“…The following plasmids were used : pIRE LUC containing two copies of the IL-6 response element (IRE) of the ICAM-1 promoter in front of the herpes simplex virus thymidine kinase promoter and the luciferase gene [41] ; pSG5-STAT3 which expresses STAT3 from the SV40 promoter ; pSG5-STAT3β, which expresses a dominant-negative isoform of STAT3 lacking the 55 C-terminal amino-acid residues ; pSG5-STAT3 Ser(#( Ala, which expressed a mutant STAT3 in which the Ser(#( is replaced by Ala ; pCS2j-RacN17 and pCS2j-RacV12 expressing the dominant-negative and constitutive-active mutant variants of Rac ; pSEK-1\MKK-4(A-L) which expresses dominant-negative SEK-1\MKK-4 [42] ; pCDNA3-MEKK∆(K432M) which expresses a dominant-negative MEKK [43] ; pCDNA3-HA-JNK-1 which expresses HA-tagged JNK-1 (p46) ; pGEX-1-cJun(1-135) expressing glutathione S-transferase (GST)-c-Jun ; and the dominant-negative and constitutive-active mutants pEFmyc-Vav-C [44] and pMEX-myc-Vav-A(∆1-65) [39,45]. The expression vector encoding a dominant-negative mutant of Raf kinase, N∆Raf, was provided by Dr P. Coffer (Department of Pulmonary Diseases, University Hospital Utrecht, Utrecht, The Netherlands) [46].…”
Section: Expression and Reporter Constructsmentioning
confidence: 99%
“…The following plasmids were used : pIRE LUC containing two copies of the IL-6 response element (IRE) of the ICAM-1 promoter in front of the herpes simplex virus thymidine kinase promoter and the luciferase gene [41] ; pSG5-STAT3 which expresses STAT3 from the SV40 promoter ; pSG5-STAT3β, which expresses a dominant-negative isoform of STAT3 lacking the 55 C-terminal amino-acid residues ; pSG5-STAT3 Ser(#( Ala, which expressed a mutant STAT3 in which the Ser(#( is replaced by Ala ; pCS2j-RacN17 and pCS2j-RacV12 expressing the dominant-negative and constitutive-active mutant variants of Rac ; pSEK-1\MKK-4(A-L) which expresses dominant-negative SEK-1\MKK-4 [42] ; pCDNA3-MEKK∆(K432M) which expresses a dominant-negative MEKK [43] ; pCDNA3-HA-JNK-1 which expresses HA-tagged JNK-1 (p46) ; pGEX-1-cJun(1-135) expressing glutathione S-transferase (GST)-c-Jun ; and the dominant-negative and constitutive-active mutants pEFmyc-Vav-C [44] and pMEX-myc-Vav-A(∆1-65) [39,45]. The expression vector encoding a dominant-negative mutant of Raf kinase, N∆Raf, was provided by Dr P. Coffer (Department of Pulmonary Diseases, University Hospital Utrecht, Utrecht, The Netherlands) [46].…”
Section: Expression and Reporter Constructsmentioning
confidence: 99%
“…Phosphorylation of JNK was also detectable after stimulation with either PMA or fMLP, which was consistently decreased in fMLP-activated rac2 Ϫ/Ϫ cells. Previous studies have suggested that Rac is downstream of phosphoinositide-3 kinase (PI3K) activation induced by chemoattractants and other signals (39,40). In rac2 Ϫ/Ϫ mast cells, PI3K activation by stem cell factor is normal, but phosphorylation of PI3-dependent kinase Akt (41) is decreased (29).…”
Section: Activation Of Intracellular Kinases In Activated Murine Neutmentioning
confidence: 99%
“…Although several studies show that Rac is activated by PI3-kinase, and many studies give evidence for a control of PI3-kinase by Rac, our findings are in line with the recent observation that in a murine T cell line inhibition of Rho GTPases by C. difficile toxin B attenuates PI3-kinase activity (60). By contrast, in CD5-stimulated T-cells, it was shown that Vav and Rac function downstream of PI3-kinase, i.e., inhibition by wortmannin could be overcome by overexpression of constitutively active Vav or Rac (61). In bone marrow-derived mast cells (BMMC), it was shown that PI3-kinase is involved in activation of the Rac/Jun kinase pathway (62).…”
Section: Figurementioning
confidence: 99%